Parenchimatous lung hamartoma in 42-year-old woman - Ileana Franco Zunda; Alfredo B. Quiñones Ceballos; Caridad Socorro Castro (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The pulmonary hamartoma, described in 1904, is presented as a mass of 3 cm of diameter and endobronchial or parenchymatous location. The lesion is registered in men two or three times more than in women, and is diagnosed generally over 60 years of age, always casually or appears in necropsies. A non frequent case of this disease is reported in a 42 year old woman. The macro-microscopic frame of the studied biopsic specimen is described, as well as its clinical conditions.